Providing Interoperability between Wearable Devices and FHIR-based Healthcare Systems - Cabral, Arthur T.; Fischer, Gabriel Souto; Righi, Rodrigo da Rosa; Costa, Cristiano A. da; Roehrs, Alex; Rigo, Sandro José; Mello, Blanda (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2024)
The manufacturers of IoT-based wearable devices present different ways to deliver the captured vital signs. Healthcare third-party systems need to adapt to the different approaches, rising complexity and acts against any idea of seamless integration. In addition to the interoperability problem, we observed that the state-of-the-art does not present alternatives that capture and analyze vital signs in such a way that they can be used to diagnose the user’s health status automatically. This article presents the HealthTranslator model, which provides interoperability by integrating multiple wearable devices and delivering their data through an HL7 FHIR healthcare standard format. More precisely, our contribution combines different user-oriented periodicity strategies to collect vital signs with data enrichment over an FHIR file, effortlessly delivering valuable insights regarding the user’s health status. We developed a microservices-based prototype that collects data on different APIs from different companies/wearables. The resources were encouraging, where data from Xiaomi, Apple, Garmin, and Samsung devices were read and delivered in an FHIR format. Thinking at the intelligent cities level, the provided interoperability is essential to generate the new vision of healthcare, where users and patients will be 24/7 monitored from their own homes.